Execution Measurement in Sharia Enterprise and Conventional Theory Perspective - Iristian, Jovi; Muhja, Zainal Abidin; Junaidi, Heri; Yulaeli, Tri; Nguyen, Phong Thanh (International Journal of Psychosocial Rehabilitation, 2020)
The presentation estimation model ought to have the option to quantify material and non-material viewpoint. Non-material angle alludes to what can be utilized as an apparatus to legitimize moral (otherworldly) powers that have been minimized in customary bookkeeping. Sharia bookkeeping is situated to the interests of partners instead of to the interests of investors. Sharia bookkeeping isn’t just a type of the executives responsibility to the proprietors of the organization (investors), yet additionally as responsibility to partners and Allah. This is on the grounds that in the perspective on big business hypothesis, the presence of an organization doesn’t just originate from the commitment of the organization’s members, for example, representatives, loan bosses, the administration, and the network. The presence of the organization is likewise dictated by the communication of the organization with the network as an outcome of the implicit understanding completed by the organization with the network.